2019
DOI: 10.1123/ijspp.2017-0773
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Pleasure and Attentional Focus on Performance and Pacing Strategies in Elite Individual Time Trials

Abstract: Mean PO during elite ITT is directly related to the athletes' ability to optimally regulate pace throughout the event. This pacing regulation is influenced by attentional focus and pleasure, underlining that coaches and athletes should devote greater attention to these psychological parameters in order to improve their performances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…34 Previous research examining the influence of pre-performance emotions on performance factors during competition 3 has predominantly relied upon analyses conducted at the between-person level. In particular, research attempting to examine the role of affect during cycling TTs 8,10 has examined effects at the group level and may have failed to detect influential individual differences at the intrapersonal level. Future psychophysiological experimental research may benefit from approaches to data analysis that are sensitive to variation and trends at the individual level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Previous research examining the influence of pre-performance emotions on performance factors during competition 3 has predominantly relied upon analyses conducted at the between-person level. In particular, research attempting to examine the role of affect during cycling TTs 8,10 has examined effects at the group level and may have failed to detect influential individual differences at the intrapersonal level. Future psychophysiological experimental research may benefit from approaches to data analysis that are sensitive to variation and trends at the individual level.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research exploring temporal aspects of emotions and affect in sport have predominantly collected psychophysiological measurements in the moments preceding competition 6,7 and/or following the completion of sport-related tasks. 8 Attempts to investigate the experience of emotions and affective states during competition have relied upon the recounting of critical incidents in qualitative interviews, 9 the completing of questionnaires immediately following a match, 3 and the use of techniques such as video-assisted recall. 2 However, the research designs used in these studies limit their ability to simultaneously record athletes' physiological responses and affective states as they occur in real time and in relation to performance demands.…”
mentioning
confidence: 99%
“…It is worth noting that athletes' time trial performance and pacing can be influenced by their affective state and attentional focus. 23 During the completion of a cycling time trial, wherein a high workload over a prolonged duration is required, physiological sensations are overwhelmingly salient and an associative attention focus is virtually unavoidable. 24 An internal attentional focus on core components of cycling and pacing has been linked with optimal performance 25 ; however, during the combined trial participants were required to focus on the external task of completing the cognitive tests, which may have diverted attention from cycling and subsequently reduced power output.…”
Section: Discussionmentioning
confidence: 99%
“…Music is a sensory input easily found in real-world exercise scenarios, as athletes from different modalities and performance levels listen to music during exercise bouts in training sessions [9][10][11][12]. For example, different from professional highly-trained athletes who may prefer to avoid distraction from exercise-related bodily sensations [13,14], recreational cyclists may listen to music as an ergogenic aid for indoor and outdoor exercises [14][15][16], as music reduces the focus from exercise-derived aversive sensations and attenuates RPE at comparable exercise intensities [17,18]. Despite controversial results [15], studies have found improved time trial performance with varied effects on pacing when participants listen to music during exercise [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%